Ligninolytic enzymes and its mechanisms for degradation of lignocellulosic waste in environment - Adarsh Kumar; Ram Chandra (Heliyon, 2020)
Ligninolytic enzymes play a key role in degradation and detoxification of lignocellulosic waste in environment. The major ligninolytic enzymes are laccase, lignin peroxidase, manganese peroxidase, and versatile peroxidase. The activities of these enzymes are enhanced by various mediators as well as some other enzymes (feruloyl esterase, aryl-alcohol oxidase, quinone reductases, lipases, catechol 2, 3-dioxygenase) to facilitate the process for degradation and detoxification of lignocellulosic waste in environment. The structurally laccase is isoenzymes with monomeric or dimeric and glycosylation levels (10–45%). This contains four copper ions of three different types. The enzyme catalyzes the overall reaction: 4 benzenediol + O2 to 4 benzosemiquinone + 2H2O. While, lignin peroxidase is a glycoprotein molecular mass of 38–46 kDa containing one mole of iron protoporphyrin IX per one mol of protein, catalyzes the H2O2 dependent oxidative depolymerization of lignin. The manganese peroxidase is a glycosylated heme protein with molecular mass of 40–50kDa. It depolymerizes the lignin molecule in the presence of manganese ion. The versatile peroxidase has broad range substrate sharing typical features of the manganese and lignin peroxidase families. Although ligninolytic enzymes have broad range of industrial application specially the degradation and detoxification of lignocellulosic waste discharged from various industrial activities, its large scale application is still limited due to lack of limited production. Further, the extremophilic properties of ligninolytic enzymes indicated their broad prospects in varied environmental conditions. Therefore it needs more extensive research for understanding its structure and mechanisms for broad range commercial applications.